Phenol resin foam, method for producing the same, and insulating material comprising the same

A phenolic resin foam with controlled composition and properties addresses acidity and thickness issues, providing stable thermal insulation and durability by maintaining low acidity and uniformity, thus preventing metal corrosion.

JP2025001016AActive Publication Date: 2025-01-07LG HAUSYS LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024176193
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-10-07
Publication Date
2025-01-07
Estimated Expiration
2040-01-17

AI Technical Summary

Technical Problem

Phenolic resin foams with acidic curing agents cause corrosion of surrounding metal materials and compromise thermal insulation performance due to high acidity and non-uniform thickness.

Method used

A phenolic resin foam with a pH of 4 or higher, produced by a composition including phenolic resin, blowing agent, and curing agent, is formulated to maintain low acidity, uniform thickness, and excellent thermal conductivity through precise control of viscosity, moisture content, and vapor pressure of the foamable composition.

Benefits of technology

The phenolic resin foam achieves low acidity, uniform thickness, high compressive strength, and effective thermal insulation, preventing metal corrosion and ensuring stable performance over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001016000001_ABST
    Figure 2025001016000001_ABST
Patent Text Reader

Abstract

To provide a phenolic resin foam that has a low acidity of pH 4 or higher, and at the same time can implement physical properties such as excellent durability and thermal conductivity with a uniform thickness.SOLUTION: There is provided a phenolic resin foam which is a thermosetting product of a foamable composition containing a phenolic resin, a foaming agent, a curing agent, and a cross-linking agent and has a pH of 4 or more. A mass ratio of carbon to sulfur (C / S) measured by EDX (energy dispersive X-ray analysis) at the vertex of the cell of the phenolic resin foam is 25 to 250, and a mass ratio of oxygen to sulfur (O / S) measured by EDX at the vertex of the cell of the phenolic resin foam is 5 to 60.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phenolic resin foam, a method for producing the same, and an insulating material containing the same. [Background technology]

[0002] The insulation material includes thermosetting foam, and by installing the insulation material on the walls of a building, it prevents heat transfer, thereby reducing the impact of external temperature changes on the internal temperature of the building, making it possible to maintain a constant indoor temperature with less energy.

[0003] A thermosetting foam is a cured product of a foamable composition, and the foamable composition contains a curing agent, which can cure the foam layer to impart appropriate closed cell ratio and mechanical properties. Meanwhile, phenolic resin foams containing a curing agent are known to have acidity, and such highly acidic phenolic resin foams may have a problem in that when exposed to water, such as rainwater, during use, highly acidic extractables are released from the foam, corroding surrounding metal materials.

[0004] For this reason, a basic inorganic filler or the like can be added to the foamable composition to neutralize the acidity of the thermosetting foam. However, the basic inorganic filler will pre-neutralize with the curing agent, resulting in a decrease in foaming performance and an increase in thermal conductivity. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a phenolic resin foam having low acidity of pH 4 or more, uniform thickness, and excellent physical properties such as durability and thermal conductivity.

[0006] Another object of the present invention is to provide a method for producing the phenolic resin foam.

[0007] It is still another object of the present invention to provide a heat insulating material containing the phenolic resin foam.

[0008] In one embodiment of the present invention, there is provided a phenolic resin foam, which is a thermosetting product of a foamable composition including a phenolic resin, a foaming agent, and a curing agent, and has a pH of 4 or more.

[0009] In another embodiment of the present invention, there is provided a method for producing a phenolic resin foam, the method comprising: preparing a foamable composition including a phenolic resin, a foaming agent, and a curing agent; and applying heat to the foamable composition to foam and cure it.

[0010] In yet another embodiment of the present invention, there is provided a thermal insulation material comprising the phenolic resin foam. Effect of the Invention

[0011] The phenolic resin foam has low acidity of pH 4 or more, and has a uniform thickness and can exhibit excellent physical properties such as durability and thermal conductivity. [Brief description of the drawings]

[0012] [Figure 1] 2 is a scanning electron microscope (SEM) image of a phenolic resin foam according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a method for measuring the thickness deviation of the phenolic resin foam of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The advantages and features of the present invention, as well as the methods for achieving them, will become clear with reference to the following examples. However, the present invention is not limited to the examples disclosed below, and may be embodied in various different forms. However, the examples are provided to fully disclose the present invention and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is only defined by the scope of the claims.

[0014] In the drawings, the thicknesses of layers and regions are exaggerated for clarity, and the thicknesses of some layers and regions are exaggerated for ease of explanation. The same reference numerals refer to the same elements throughout the specification.

[0015] In addition, when a part such as a layer, film, region, plate, etc. is referred to herein as being "on" or "above" another part, this includes not only the case where it is "directly on" another part, but also the case where there is another part in between. Conversely, when a part is referred to as being "directly on" another part, it means that there is no other part in between. In addition, when a part such as a layer, film, region, plate, etc. is referred to herein as being "under" or "below" another part, this includes not only the case where it is "directly below" another part, but also the case where there is another part in between. Conversely, when a part is referred to as being "directly below" another part, it means that there is no other part in between.

[0016] In one embodiment of the present invention, there is provided a phenolic resin foam, which is a thermosetting product of a foamable composition including a phenolic resin, a foaming agent, and a curing agent, and has a pH of 4 or more.

[0017] Generally, a thermosetting foam contains a curing agent, and the foam layer is cured to give it an appropriate closed cell ratio and mechanical properties. However, a thermosetting foam containing a curing agent, for example, a phenolic resin foam, contains a highly acidic curing agent, which may cause problems such as a low pH of the thermosetting foam and corrosion of surrounding metal materials due to the highly acidic thermosetting foam. In addition, if the content of the curing agent is reduced to produce a low-acid thermosetting foam, it becomes difficult to control the foaming performance and curing performance, and the balance is broken, and problems such as poor appearance of the thermosetting foam and high thermal conductivity may occur. In addition, if a phenolic resin with high reactivity is used or the curing temperature is increased to improve this, it may be difficult to produce a thermosetting foam having a uniform thickness of a certain level.

[0018] The phenolic resin foam of the present invention includes a thermosetting product of a foamable composition including a phenolic resin, a foaming agent, and a curing agent, and the composition is adjusted to have a uniform thickness, excellent durability and thermal conductivity, and low acidity of pH 4 or more. Specifically, the pH of the phenolic resin foam may be 4 to 7, 4.5 to 7, or 5 to 6. The phenolic resin foam has a high closed cell ratio, a uniform thickness, excellent compressive strength, and thermal conductivity, and exhibits excellent heat insulating performance. In addition, the low acidity in the pH range allows the phenolic resin foam to be produced more stably, and the phenolic resin foam can be used more stably for a long period of time because it does not corrode surrounding metals, etc.

[0019] The foamable composition includes a phenolic resin obtained by reacting phenol with formaldehyde, and may include, for example, a resol-based phenolic resin.

[0020] The foamable composition may contain the phenolic resin in an amount of about 30% by weight to about 90% by weight. By containing the phenolic resin in an amount within this range, foam cells can be stably formed and excellent thermal conductivity can be realized. Specifically, if the phenolic resin is contained in an amount less than this range, it is difficult to form foam cells and the thermal conductivity is high, and if it exceeds this range, the proportion of other additives is relatively low, which may cause defects in the shape of the foam cells or in the foaming process.

[0021] The phenolic resin may have a viscosity of about 1,000 cps to about 30,000 cps, specifically, about 2,000 cps to about 10,000 cps, more specifically, about 3,000 cps to about 7,000 cps, under a temperature condition of about 40° C. The viscosity may be measured using a Brookfield viscometer.

[0022] The foamable composition includes a phenolic resin having a viscosity in the above range, and the foaming performance can be suitably adjusted, whereby foam cells are well formed, the closed cell rate is improved, and excellent thermal conductivity can be imparted. Specifically, if the viscosity of the phenolic resin is below the above range, loss of foaming gas may occur at the beginning of foaming, which may increase thermal conductivity and reduce heat insulation. In addition, if the viscosity exceeds the above range, the curing speed becomes faster than the foaming speed, and foam cells having a suitable size are not well formed, which may cause a problem that the foam cannot be formed to a desired thickness or more.

[0023] The phenolic resin may have a moisture content of about 5% by weight or more, specifically, about 5% by weight to about 30% by weight. More specifically, the moisture content may be about 7% by weight to about 23% by weight. The moisture content may be measured by the Karl Fischer Titration method. The phenolic resin may have a moisture content within the above range, thereby realizing excellent workability and excellent heat insulation. Specifically, if the moisture content of the phenolic resin is out of the above range and is too low, the foamable composition may not be smoothly blended with other components, making process control difficult, and if the moisture content is too high, the heat insulation may decrease and the adhesiveness of the thermosetting foam may decrease. Therefore, the phenolic resin foam may be difficult to firmly adhere to a surface material or the like by a lamination method.

[0024] In addition, the phenolic resin may not include a urea bond, which makes it easy to control the viscosity and moisture of the foamable composition since moisture is not generated by the urea-formaldehyde reaction during the polymerization process of the phenolic resin.

[0025] The foamable composition includes a curing agent. The curing agent may include one acid curing agent selected from the group consisting of toluenesulfonic acid, xylenesulfonic acid, benzenesulfonic acid, phenolsulfonic acid, ethylbenzenesulfonic acid, styrenesulfonic acid, naphthalenesulfonic acid, and combinations thereof. The foamable composition includes the curing agent and may exhibit suitable crosslinking, curing, and foaming properties.

[0026] The foamable composition may contain the curing agent in an amount of about 3 parts by weight to about 15 parts by weight based on 100 parts by weight of the phenolic resin. For example, the curing agent may be contained in an amount of about 5 parts by weight to about 12 parts by weight or about 5 parts by weight to about 10 parts by weight based on 100 parts by weight of the phenolic resin. The foamable composition contains the curing agent in such a low amount as described above, and can impart low acidity to the phenolic resin foam, and can also realize uniform thickness, excellent compressive strength, and low thermal conductivity, thereby imparting excellent heat insulating performance.

[0027] Specifically, if the content of the curing agent is less than the above range, the pH may be higher, but there may be a problem that the performance as a heat insulating material is significantly reduced, whereas if the content of the curing agent is more than the above range, there may be a problem that the acidity becomes high, i.e., the pH becomes low.

[0028] The foamable composition includes a foaming agent. The foaming agent may include one selected from the group consisting of a hydrofluoroolefin (HFO)-based compound, a hydrocarbon-based compound, and combinations thereof.

[0029] The foamable composition may contain a foaming agent having a vapor pressure of about 20 kPa to about 110 kPa at 20°C, specifically, about 30 kPa to about 100 kPa, more specifically, about 33 kPa to about 85 kPa, by adjusting the type and content of the foaming agent. The vapor pressure of the foaming agent means the inherent vapor pressure of the foaming agent at 20°C. The vapor pressure of the foaming agent can be measured by the static method of KS M 1071-3. When the foaming agent is a mixture of two or more foaming agents, the vapor pressure (Pm) of the foaming agent means a value calculated using the following relational expression 1.

[0030] [Equation 1]P m =(m1P1+m2P2+..m x P x ) / (m1+m2+..m x ) P m : Vapor pressure of the entire mixture m x : The number of moles of blowing agent x itself contained in the mixture P x : Specific vapor pressure of foaming agent

[0031] Generally, when the content of the curing agent in the foamable composition is reduced, the thermosetting foam can have low acidity. However, as the content of the curing agent is reduced, the foaming amount and foaming performance are reduced, the balance with the curing performance is broken, and problems such as the thickness of the thermosetting foam becoming non-uniform, the compressive strength being reduced, and the thermal conductivity being increased may occur.

[0032] The foamable composition contains a foaming agent having a vapor pressure in the above range, and can impart improved foaming performance, and can impart a high closed cell ratio, uniform thickness, excellent compressive strength, and excellent thermal conductivity to the phenolic resin foam having low acidity.

[0033] Specifically, when the vapor pressure of the foaming agent is less than the above range, foaming does not occur sufficiently, making it difficult to obtain a phenolic resin foam of a specified thickness, and there may be a problem of a large thickness deviation at different positions in the phenolic resin foam. When the vapor pressure of the foaming agent exceeds the above range, foaming occurs too quickly, reducing the closed cell ratio and rupturing the foam cells of the phenolic resin foam, resulting in a decrease in physical strength and an increase in thermal conductivity.

[0034] The hydrofluoroolefin-based compound may include, for example, a chlorinated hydrofluoroolefin-based compound, a non-chlorinated hydrofluoroolefin-based compound, or all of these.

[0035] The hydrofluoroolefin-based compound may be of a type known in the art, such as trans 1-chloro-3,3,3-trifluoropropene (trans CFCH=CClH), cis 1-chloro-3,3,3-trifluoropropene (cis CFCH=CClH), trans 1-chloro-2,3,3-trifluoropropene (trans CHFCF=CClH), cis 1-chloro-2,3,3-trifluoropropene (cis CHFCF=CClH), trans 1-chloro-1,3,3-trifluoropropene (trans CHFCH=CClF), cis 1-chloro-1,3,3-trifluoropropene (cis CHFCH=CClF), trans 2-chloro-1,3,3-trifluoropropene (trans CHFCCl=CHF), cis 2-chloro-1,3,3-trifluoropropene (cis CHF2CCl=CHF), trans 2-chloro-1,1,3-trifluoropropene (trans CH2FCCl=CF2), cis 2-chloro-1,1,3-trifluoropropene (cis CH2FCCl=CF2), trans 3-chloro-1,2,3-trifluoropropene (trans CHFClCF=CFH), cis 3-chloro-1,2,3-trifluoropropene (cis CHFClCF=CFH), trans 3-chloro-1,1,2-trifluoropropene (trans CH2ClCF=CF2), cis 3-chloro-1,1,2-trifluoropropene (cis CH2ClCF=CF2), trans 3-chloro-2,3,3-trifluoropropene (trans CF2ClCF=CH2), cis 3-chloro-2,3,3-trifluoropropene (cis monochlorotrifluoropropenes such as 2,3,3-trifluoropropene (CHF2CF=CH2), 1,1,2-trifluoropropene (CH3CF=CF2), 1,1,3-trifluoropropene (CH2FCH=CF2), 1,3,3-trifluoropropene (CHF2CH=CHF), etc.;Tetrafluoropropenes such as 1,2,3,3-tetrafluoro-1-propene, 2,3,3,3-tetrafluoro-1-propene, 1,3,3,3-tetrafluoro-1-propene, 1,1,2,3-tetrafluoro-1-propene, 1,1,3,3-tetrafluoro-1-propene, 1,2,3,3-tetrafluoro-1-propene; pentafluoropropenes such as 1,2,3,3,3-pentafluoro-1-propene, 1,1,3,3,3-pentafluoro-1-propene, 1,1,2,3,3-pentafluoro-1-propene; 2,3,3,4,4,4-hexafluoro-1-butene, 1,1,1,4,4, 4-hexafluoro-2-butene, 1,3,3,4,4,4-hexafluoro-1-butene, 1,2,3,4,4,4-hexafluoro-1-butene, 1,2,3,3,4,4-hexafluoro-1-butene, 1,1,2,3,4,4-hexafluoro-2-butene, 1,1,1,2,3,4-hexafluoro-2-butene, 1,1,1,2,3,3-hexafluoro-2-butene, 1,1,1,3,4,4-hexafluoro-2-butene, 1,1,2,3,3,4-hexafluoro-1-butene, and combinations thereof.

[0036] The hydrocarbon-based compound may contain a hydrocarbon having 1 to 6 carbon atoms, and may contain, for example, a chlorinated hydrocarbon compound, a non-chlorinated hydrocarbon compound, or all of these.

[0037] The hydrocarbon compound may include at least one selected from the group consisting of dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, isopentyl chloride, n-butane, isobutane, n-pentane, isopentane, cyclopentane, n-hexane, and combinations thereof, but is not limited thereto.

[0038] The blowing agent may be a mixture of two or more of the blowing agents. Specifically, the mixed blowing agent includes a hydrofluoroolefin (HFO)-based compound, and can provide excellent foaming performance even with a low calorific value. For example, the blowing agent may be a mixture of one hydrofluoroolefin-based compound selected from the group consisting of 1-chloro-3,3,3-trifluoropropene (CF3CH=CClH), 1,1,1,4,4,4-hexafluoro-2-butene, and combinations thereof, and one hydrocarbon-based compound selected from the group consisting of cyclopentane, isopentane, n-pentane, n-hexane, n-butane, and combinations thereof.

[0039] The foaming agent may be included in a total amount of about 5 parts by weight to about 15 parts by weight based on about 100 parts by weight of the phenolic resin. By including the foaming agent in this range, it is possible to provide the phenolic resin foam with low acidity, uniform thickness, excellent compressive strength, and excellent thermal conductivity, while exhibiting excellent foaming performance even with a low calorific value.

[0040] Specifically, if the content of the foaming agent is less than the above range, there may be a problem that the foaming agent does not vaporize due to an insufficient content, or the foaming does not occur sufficiently, so that the desired thickness is not achieved, or the thickness deviation at each position of the phenolic resin foam increases. If the content of the foaming agent is more than the above range, there may be a problem that an excessive amount of the foaming agent vaporizes, making it difficult to control the vapor pressure of the foaming agent, or that the foaming pressure becomes too high, causing the foam cells of the phenolic resin foam to break, resulting in a low closed cell ratio, a low physical strength, and an high thermal conductivity.

[0041] The foamable composition may further comprise a crosslinker selected from the group consisting of resorcinol, cresol, saligenin, p-methylolphenol, and combinations thereof.

[0042] Generally, when the content of the curing agent in the foamable composition is reduced, the thermosetting foam can have low acidity. However, as the content of the curing agent is reduced, the curing performance is reduced, and the balance with the foaming performance is broken, which may cause phenomena such as foam cell rupture, and cracks may occur in the thermosetting foam, resulting in uneven thickness and high thermal conductivity.

[0043] The foamable composition further contains the crosslinking agent together with the curing agent, and maintains the low acidity of the phenolic resin foam while imparting excellent crosslinking and curing performance, thereby making the thickness of the phenolic resin foam uniform and imparting excellent durability such as compressive strength and excellent thermal conductivity.

[0044] Specifically, the foamable composition may contain the curing agent and the crosslinking agent in a weight ratio of about 6:4 to about 3:7. For example, the foamable composition may contain the curing agent and the crosslinking agent in a weight ratio of about 6:4 to 4:9 or about 5:6 to 4:9. If the content of the crosslinking agent is less than the above range, the crosslinking and curing reaction may be insufficient, resulting in high thermal conductivity and low compressive strength. If the content of the crosslinking agent is more than the above range, the foam may be cured without sufficient foaming, resulting in breakage of foam cells, low closed cell ratio, large thickness deviation at each position of the phenolic resin foam, and high thermal conductivity.

[0045] The phenolic resin foam may have a carbon to sulfur mass ratio (C / S) of 25 to 250 at the vertex of a cell, as measured by EDX (energy dispersive X-ray analysis).

[0046] 1 is a scanning electron microscope (SEM) photograph of a phenolic resin foam according to an embodiment of the present invention, and as shown in Fig. 1, cells included in the phenolic resin foam have cell walls 10 and struts 20 formed at points where the cell walls abut, and the struts 20 constitute the skeleton of the cells. In addition, the intersections where the struts 20 meet are defined as cell vertices 30.

[0047] The cross section of the phenolic resin foam at the middle of the width, length and height, i.e., the center part, for example, a cross section of a panel type foam bisected in the thickness direction, was magnified 200 times with a scanning electron microscope (SEM), and only C, O and S elements were selected at the vertex of the cell of the cross section and the proportions of these three elements were measured with EDX (manufacturer Horiba, EMAX EX-250, accelerating voltage 15 kv).

[0048] Specifically, n cells that are not adjacent to each other were selected based on any one cell included in the cross section, and the ratios of C, O, and S elements at one vertex included in each cell were measured. In addition, the mass ratio of carbon to sulfur (C / S) was measured by setting the sum of the ratios of C, O, and S elements measured at the vertex of each cell as 100%. The mass ratio of carbon to sulfur (C / S) refers to the sum of the C / S values ​​at one vertex included in the 1st to nth cells divided by n. That is, the mass ratio of carbon to sulfur (C / S) can be calculated using the following Equation 1.

[0049]

number

[0050] In this case, n is an integer of 7 to 10. Preferably, n is an integer of 9 to 10 or n is 10.

[0051] The phenolic resin foam is a thermosetting product of the foamable composition, and the foamable composition may be adjusted so that the vertex of a cell has a carbon to sulfur mass ratio (C / S) of about 25 to about 250, about 50 to about 150, or about 69 to about 123, as measured by EDX.

[0052] The sulfur may be an element derived from the curing agent, and the phenolic resin foam may have a mass ratio of carbon to sulfur (C / S) in the above range, relative to the carbon (C) contained in the phenolic resin foam, which is a thermoset product of the foamable composition containing the foaming agent.

[0053] If the mass ratio of carbon to sulfur (C / S) is less than the above range, an acidic foam having a high acidity and low pH may be formed. If the mass ratio exceeds the above range, curing during the foaming process may not be sufficient, resulting in low physical strength of the phenolic foam, cracks on the surface, uneven thickness, low compressive strength, and high thermal conductivity.

[0054] The phenolic resin foam may have a mass ratio of oxygen to sulfur (O / S) of about 5 to about 60, measured by EDX at the vertex of a cell. The mass ratio of oxygen to sulfur (O / S) refers to a value obtained by dividing the sum of O / S values ​​of one vertex included in the 1st to nth cells by n. That is, the mass ratio of oxygen to sulfur (O / S) can be calculated using the following Equation 2.

[0055]

number

[0056] In this case, n is an integer of 7 to 10. Preferably, n is an integer of 9 to 10 or n is 10.

[0057] The phenolic resin foam is a thermosetting product of the foamable composition, and the foamable composition may be adjusted so that the mass ratio of oxygen to sulfur (O / S) measured at the vertex of a cell by EDX may be about 5 to about 60, or about 10 to about 50, or about 19 to about 33.

[0058] The sulfur is an element derived from the curing agent, and compared to the oxygen (O) contained in the phenolic resin foam, which is a thermoset of the foamable composition containing the phenolic resin, a specific curing agent, a crosslinking agent, etc., the phenolic resin foam may have a mass ratio of oxygen to sulfur (O / S) within the above range.

[0059] If the mass ratio of oxygen to sulfur (O / S) is less than the above range, the foaming is not sufficiently performed before curing, and in this process, the acidity (pH) of the phenolic resin foam may be low or the thickness may be non-uniform, resulting in high thermal conductivity.If the mass ratio exceeds the above range, the curing performance may be insufficient, resulting in low physical strength of the phenolic resin foam and high thermal conductivity.

[0060] The phenolic resin foam may have an average thickness of about 70 mm to about 300 mm. The phenolic resin foam has an average thickness within the above range, so that the total thickness of the thermal insulation material for building containing the phenolic resin foam is not excessively increased, and the thermal insulation property of a sufficiently excellent level can be realized. Specifically, when the average thickness of the phenolic resin foam is less than the above range, the thermal conductivity is low and the foam cannot function as a thermal insulation material for building, and when the average thickness exceeds the above range, the heat generated during the curing process accumulates in the inner center of the foam, preventing the formation of a cell structure and decreasing the thermal conductivity.

[0061] The phenolic resin foam may have a thickness deviation of about 5% or less, specifically, about 0.1% to about 5%, as determined by the following Equation 3:

[0062] [Formula 3] Thickness deviation (T d ,%)=(Tmax -T min ) / T avg ×100

[0063] In the above formula 3, the T max means the maximum thickness measured for the foam for which the thickness deviation is to be measured, and min means the minimum thickness measured on the foam, T avg means the average thickness measured on the foam.

[0064] The phenolic resin foam has a thickness deviation within the above range, and is found to have excellent thickness uniformity, thereby exhibiting excellent thermal conductivity, effectively improving long-term heat insulation, and providing excellent processability and workability when applied to a specific product. For example, the phenolic resin foam may have a thickness deviation of about 0.1% to about 3%, or 0.1% to 2.4%.

[0065] The phenolic foam may have a thermal conductivity of about 0.0160 W / m·K to about 0.0220 W / m·K measured through the thickness at a temperature of about 20° C. according to KS L 9016. For example, the phenolic foam may have a thermal conductivity of about 0.0164 W / m·K to about 0.0210 W / m·K, about 0.0164 W / m·K to less than about 0.020 W / m·K, or about 0.0164 W / m·K to about 0.0194 W / m·K.

[0066] Generally, the thicker the foam, the lower the thermal conductivity measured in the thickness direction. As described above, the phenolic resin foam has a sufficiently large thickness and does not lower the thermal conductivity, so that it can maintain excellent heat insulation.

[0067] The phenolic resin foam may have a density of about 20 kg / m3 to about 50 kg / m3. By having a density in this range, the phenolic resin foam is easy to handle on-site and can realize excellent physical strength and excellent heat insulating performance.

[0068] The phenolic resin foam may have a compressive strength of about 100 kPa to about 300 kPa according to KS M ISO 844. The phenolic resin foam may be a cured product of the foamable composition produced by adding the curing agent, the foaming agent, the crosslinking agent, etc. to the phenolic resin, and may have a compressive strength in the above range. If the compressive strength of the phenolic resin foam is less than the above range, the phenolic resin foam may be easily deformed in appearance when handled, such as when cut or applied, and may have problems with long-term durability, such as being easily broken when used, and if it exceeds the above range, the phenolic resin foam may have a high density and a high thermal conductivity.

[0069] The phenolic resin foam may have a closed cell ratio of about 85% or more. The phenolic resin foam is composed of small ham-comb-shaped cells, and the percentage of closed cells among the cells is called the closed cell ratio. The higher the closed cell ratio, the better the thermal insulation, and if the closed cell ratio is less than about 85%, a certain level of thermal insulation cannot be ensured. There is no upper limit to the closed cell ratio, but the phenolic resin foam may have a closed cell ratio of about 99%.

[0070] Another embodiment of the present invention provides a method for producing a phenolic resin foam, the method comprising: preparing a foamable composition including a phenolic resin, a foaming agent, and a curing agent; and applying heat to the foamable composition to foam and cure it.

[0071] The above-mentioned phenolic resin foam can be produced by the above-mentioned production method.

[0072] In the above-mentioned manufacturing method, a foamable composition including a phenolic resin, a foaming agent, and a curing agent is prepared. Specific details of the foamable composition are as described above.

[0073] Specifically, the foamable composition may be prepared by first mixing the phenolic resin and the foaming agent, and then adding the curing agent to the mixture. In this case, when the foamable composition further includes a crosslinking agent, the crosslinking agent may be added to the mixture and mixed together, and then the curing agent may be added.

[0074] The method also includes a step of applying heat to the prepared foamable composition to foam and cure it. The foamable composition can be foamed and cured simultaneously, and in this case, either foaming or curing can be started first, or both can be started simultaneously.

[0075] The foaming and curing can be carried out under temperature conditions, for example, from about 50° C. to about 90° C. The foaming and curing can be carried out for about 2 minutes to about 20 minutes, but is not limited thereto, and may suitably differ depending on the purpose and use of the invention.

[0076] The foamable composition may be, for example, foamed and cured in a predetermined mold, or may be, for example, foamed and cured while being injected or discharged between both surface materials, but is not limited thereto, thereby producing the above-mentioned phenolic resin foam.

[0077] Yet another embodiment of the present invention provides a thermal insulation material comprising the phenolic resin foam.

[0078] The phenolic resin foam is a low-acid phenolic resin foam having a pH of 4 or more, and can be used, for example, as a building insulation material. Even when exposed to water such as rainwater, it does not corrode surrounding metal materials, and can simultaneously satisfy the high thickness standard, excellent durability, and excellent thermal conductivity required for a building insulation material.

[0079] The architectural insulation material may further include a surface material on one or both sides of the phenolic resin foam, and the surface material may be of a type known in the art, such as, but not limited to, woven fabric, nonwoven fabric, cloth derived from organic or inorganic substances, metal foil such as aluminum, paper, etc.

[0080] Specific examples of the present invention are presented below. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereby.

[0081] <Examples and Comparative Examples> Example 1 A resol-based phenolic resin having a viscosity of 3,900 cps under a temperature condition of 40°C was prepared at a temperature of 20°C. In addition, a resin mixture was prepared by mixing trans-1-chloro-3,3,3-trifluoropropene (trans CF3CH=CClH) and cyclopentane in a weight ratio of 7:3 with respect to 100 parts by weight of the resol-based phenolic resin, 10 parts by weight of a foaming agent having a vapor pressure of about 74 kPa at 20°C, 3 parts by weight of a surfactant polyoxyethylene sorbitan ester, and 36 parts by weight of a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5. In addition, toluene sulfonic acid was prepared in an amount of 8 parts by weight with respect to 100 parts by weight of the resol-based phenolic resin, and then mixed with water in a weight ratio of 8:2 and added to the resin mixture to prepare a foamable composition. The foamable composition was kneaded at 2000 rpm to form a white foam-like slurry. The white foam was then poured into a 300×300×90 mm mold with a density of 40 kg / m 3 The mixture was filled to a weight of 100 g, heated in an oven at 70° C. for 10 minutes, and then the mold was separated to finally produce a phenolic resin foam.

[0082] Example 2 A phenolic resin foam was manufactured in the same manner as in Example 1, except that 1,1,1,4,4,4-hexafluoro-2-butene having a vapor pressure of about 60 kPa at 20° C. was used as a foaming agent, 24 parts by weight of a crosslinking agent mixture (polyester polyol and resorcinol) obtained by mixing polyester polyol and resorcinol in a weight ratio of 5:5 per 100 parts by weight of the resol phenolic resin, and 10 parts by weight of p-toluene sulfonic acid per 100 parts by weight of the resol phenolic resin were prepared, mixed with water in a weight ratio of 8:2, and then added to manufacture a foamable composition.

[0083] Example 3 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming agent having a vapor pressure of about 74 kPa at 20° C. was used, and a crosslinking agent mixture (polyester polyol and resorcinol) was used in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 relative to 100 parts by weight of the resol-based phenolic resin. 12 parts by weight of p-toluene sulfonic acid was prepared relative to 100 parts by weight of the resol-based phenolic resin, and the mixture was mixed with water in a weight ratio of 8:2 and then added to manufacture a foamable composition.

[0084] Example 4 A phenolic resin foam was produced in the same manner as in Example 1, except that a foamable composition was produced using a foaming agent having a vapor pressure of about 39 kPa at 20°C, which was prepared by mixing trans-1-chloro-3,3,3-trifluoropropene (trans CFCH=CClH) and cyclopentane in a weight ratio of 1:9.

[0085] Example 5 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming agent having a vapor pressure of about 37 kPa at 20°C was used, which was a mixture of trans-1-chloro-3,3,3-trifluoropropene (trans CF3CH=CClH) and cyclopentane in a weight ratio of 5:95, and a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 per 100 parts by weight of the resol-based phenolic resin was used, and toluene sulfonic acid was prepared in an amount of 12 parts by weight per 100 parts by weight of the resol-based phenolic resin, and then mixed with water in a weight ratio of 8:2 and then added to the mixture to manufacture a foamable composition.

[0086] Example 6 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming agent having a vapor pressure of about 74 kPa at 20°C was used, which was a mixture of trans-1-chloro-3,3,3-trifluoropropene (trans CFCH=CClH) and cyclopentane in a weight ratio of 7:3, and a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 relative to 100 parts by weight of the resol-based phenolic resin was used, and toluene sulfonic acid was prepared in an amount of 15 parts by weight relative to 100 parts by weight of the resol-based phenolic resin, and then mixed with water in a weight ratio of 8:2 and then added to manufacture a foamable composition.

[0087] Example 7 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming composition was manufactured by mixing trans-1-chloro-3,3,3-trifluoropropene (trans CF3CH=CClH) and cyclopentane in a weight ratio of 7:3 and having a vapor pressure of about 74 kPa at 20°C, using 15 parts by weight of a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 relative to 100 parts by weight of the resol-based phenolic resin, and preparing 5 parts by weight of p-toluene sulfonic acid relative to 100 parts by weight of the resol-based phenolic resin, mixing the mixture with water in a weight ratio of 8:2, and then adding the mixture to manufacture a foamable composition.

[0088] Example 8 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming agent having a vapor pressure of about 37 kPa at 20°C was used, which was a mixture of trans-1-chloro-3,3,3-trifluoropropene (trans CF3CH=CClH) and cyclopentane in a weight ratio of 5:95, and a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 relative to 100 parts by weight of the resol-based phenolic resin was used, and toluene sulfonic acid was prepared in an amount of 7 parts by weight relative to 100 parts by weight of the resol-based phenolic resin, and then mixed with water in a weight ratio of 8:2 and then added to the mixture to manufacture a foamable composition.

[0089] Comparative Example 1 A phenolic resin foam was prepared in the same manner as in Example 1, except that toluenesulfonic acid (p-toluene sulfonic acid) was prepared in an amount of 25 parts by weight based on 100 parts by weight of the resol-based phenolic resin, and mixed with water in a weight ratio of 8:2, and then added to the resin mixture not containing the crosslinker mixture to prepare a foamable composition.

[0090] Comparative Example 2 A phenolic resin foam was prepared in the same manner as in Example 1, except that toluenesulfonic acid (p-toluene sulfonic acid) was prepared in an amount of 12 parts by weight based on 100 parts by weight of the resol-based phenolic resin, and mixed with water in a weight ratio of 8:2. The mixture was then added to the resin mixture not containing the crosslinker mixture to prepare a foamable composition.

[0091] Comparative Example 3 A phenolic resin foam was manufactured in the same manner as in Example 1, except that a foaming composition was manufactured using 8 parts by weight of trans-1-chloro-3,3,3-trifluoropropene (trans CF3CH=CClH) alone having a vapor pressure of about 154 kPa at 30°C, 33.2 parts by weight of a crosslinking agent mixture (polyester polyol and resorcinol) in which polyester polyol and resorcinol were mixed in a weight ratio of 5:5 relative to 100 parts by weight of the resol phenolic resin, and 5 parts by weight of p-toluene sulfonic acid was prepared relative to 100 parts by weight of the resol phenolic resin, which was then mixed with water in a weight ratio of 8:2 and then added to the mixture.

[0092] <Evaluation> Experimental example 1: EDX (energy dispersive X-ray analysis) The center part of the phenolic resin foam of the examples and comparative examples was cut into a test piece having a size of 5 mm x 5 mm and a thickness (h = 90 mm). In addition, a cut was made in the center part (h / 2) of the test piece, and the test piece was placed in liquid nitrogen, and a force was applied to both ends of the test piece so that the cut center part was cut. For this purpose, a test piece having a cross section preserved in liquid nitrogen was prepared. Then, the test piece including the cross section was cut to a thickness of 2 mm, and the test piece preserved in liquid nitrogen was fixed on an SEM mount so that the cross section of the test piece facing upward, and was then PT coated (platinum coated). In addition, the SEM mount on which the test piece was fixed was placed in an SEM, and the screen was magnified to 200 times.

[0093] 1 is a scanning electron microscope (FE-SEM, SU8010, Hitachi) photograph of a phenolic foam according to an embodiment of the present invention, and as shown in Fig. 1, cells included in the phenolic foam have cell walls 10 and struts 20 formed at the points where the cell walls abut, and the struts 20 form the skeleton of the cells. In addition, the intersections where the struts 20 meet are defined as cell vertices 30.

[0094] In the vertex of the cell on the SEM screen, only C, O, and S elements were selected and the ratio of these three elements was measured using an EDX (energy dispersive X-ray analysis) (HORIBA, EMAX EX-250, accelerating voltage 15 kv). Specifically, based on one arbitrary cell included in the cross section, n cells (n=10) that are not adjacent to each other were selected, and the ratio of C, O, and S elements in one vertex included in each of the cells was measured.

[0095] In addition, the mass ratio of carbon to sulfur (C / S) and the mass ratio of oxygen to sulfur (O / S) were calculated using the sum of the measured proportions of C, O, and S elements as 100% using the following Formulas 1 and 2, and the results are shown in Tables 1 and 2 below.

[0096]

number

[0097] In this case, n is an integer from 7 to 10.

[0098]

number

[0099] In this case, n is an integer from 7 to 10.

[0100] Experimental example 2: pH The center part of the phenolic resin foam of the examples and comparative examples was cut into a size of 50 mm x 50 mm x 50 mm to prepare a specimen, and the specimen was immersed in 150 ml of distilled water at 20°C to 30°C so that six sides of the specimen were in contact with the distilled water, and then sealed and immersed for 48 hours. In addition, the pH of the extract obtained after removing the immersed specimen was measured using a pH meter, and the results are shown in Tables 1 and 2 below.

[0101] Experimental Example 3: Thermal Conductivity (W / mK) The phenolic resin foams of the examples and comparative examples were cut from the center to a thickness of 50 mm from the top and a size of 300 mm x 300 mm to prepare specimens, which were then pretreated by drying at 70°C for 12 hours. The thermal conductivity of the specimens was measured using a thermal conductivity instrument HC-074-300 (EKO Co.) at an average temperature of 20°C according to the measurement conditions of KS L 9016 (plate heat flow meter measurement method), and the results are shown in Tables 1 and 2 below.

[0102] Experimental Example 4: Compressive strength (kPa) The phenolic foams of the examples and comparative examples were prepared as test pieces with a size of 50 mm x 50 mm and a thickness of 90 mm, and the test pieces were placed between the wide plates of a Lloyd Instrument LF Plus Universal Testing Machine. The UTM equipment was set to a speed of 10% / min of the test piece thickness, and a compressive strength test was started to record the maximum load reached during the thickness reduction. The compressive strength was measured according to the method of KS M ISO 844 standard, and the results are shown in Tables 1 and 2 below.

[0103] Experimental Example 5: Thickness deviation (%) FIG. 2 is a schematic diagram simply illustrating a method for measuring the thickness deviation of the phenolic resin foam of the present invention.

[0104] The phenolic foam of the examples and comparative examples was prepared as a test piece having a size of 300 mm x 300 mm and a thickness of 90 mm. Then, the thickness was measured at five points at intervals of 50 mm on each of the horizontal and vertical sides of the test piece using a sliding caliper tool having an accuracy of 0.1 mm, as shown by the solid lines in FIG. 2. That is, the thickness was measured at 20 points on a total of four sides of the test piece to obtain T. avg , T max , T min The thickness deviation was measured according to the following formula 3, and the results are shown in Tables 1 and 2 below.

[0105] [Formula 3] Thickness deviation (T d ,%)=(T max -T min ) / T avg ×100

[0106] In the above formula 3, the T max means the maximum thickness measured on the foam sheet, and T min means the minimum measured thickness, T avg means the average thickness measured.

[0107] Experimental Example 6: Closed cell ratio (%) The foams of the Examples and Comparative Examples were measured using a closed cell ratio measuring device (Quantachrome, ULTRAPYC 1200e) according to the KS M ISO 4590 measurement method, and the results are shown in Tables 1 and 2 below.

[0108] [Table 1]

[0109] [Table 2]

[0110] As shown in Tables 1 and 2, Comparative Example 1, which does not fall within the range of EDX(C / S) and EDX(O / S), shows that the acidity of the phenolic resin foam is too high, and Comparative Example 2 shows that the phenolic resin foam has low acidity, but has low thermal conductivity and compressive strength and has a significant thickness deviation, even though it is a low acidity phenolic resin foam. On the other hand, it can be seen that the Examples have low acidity of pH 4 or more, uniform thickness, and excellent physical properties such as durability and thermal conductivity. [Explanation of symbols]

[0111] 10 Cell wall 20 Strut 30 cell vertex

Claims

1. A phenolic resin foam which is a thermoset of a foamable composition comprising a phenolic resin, a foaming agent, a curing agent, and a crosslinking agent, The pH is 4 or more, The vertex of the cell of the phenolic resin foam was analyzed by EDX (energy dispersive X-ray spectroscopy). The mass ratio of carbon to sulfur (C / S) measured by energy dispersive X-ray analysis (EDXA) is 25 to 250, The apex of the cell of the phenolic resin foam was analyzed by EDX (energy dispersive X-ray spectroscopy). The mass ratio of oxygen to sulfur (O / S) measured by energy dispersive X-ray analysis (E X-ray analysis) is 5 to 60; Phenolic foam.

2. The vapor pressure of the foaming agent at 20°C is 20 kPa to 110 kPa. The phenolic foam of claim 1.

3. The blowing agent includes one selected from the group consisting of hydrofluoroolefin (HFO)-based compounds, hydrocarbon-based compounds, and combinations thereof; The phenolic foam of claim 1.

4. The foamable composition contains 3 to 15 parts by weight of the curing agent relative to 100 parts by weight of the phenolic resin. The phenolic foam of claim 1.

5. The curing agent comprises one selected from the group consisting of toluene sulfonic acid, xylene sulfonic acid, benzene sulfonic acid, phenol sulfonic acid, styrene sulfonic acid, ethylbenzene sulfonic acid, naphthalene sulfonic acid, and combinations thereof; The phenolic foam of claim 1.

6. The crosslinking agent is one selected from the group consisting of resorcinol, cresol, saligenin, p-methylolphenol, and combinations thereof. The phenolic foam of claim 1.

7. the weight ratio of the curing agent to the crosslinking agent is 6:4 to 3:7; The phenolic foam of claim 1.

8. The thickness deviation according to the following formula 3 is 5% or less. The phenolic foam of claim 1 : [Formula 3] Thickness deviation (T d ,%)=(T max -T min ) / T avg ×100 In the formula 3, the T max means the maximum thickness measured for the foam for which the thickness deviation is to be measured, and min means the minimum thickness measured on the foam, T avg means the average thickness measured on the foam.

9. The thermal conductivity measured at an average temperature of 20°C according to KS L 9016 is 0.0160 W / m K to 0.0220 W / m K. The phenolic foam of claim 1.

10. Compressive strength according to KS M ISO 844 is 100 kPa to 300 kPa; The phenolic foam of claim 1.

11. providing a foamable composition comprising a phenolic resin, a foaming agent, a curing agent, and a crosslinking agent; applying heat to the foamable composition to foam and cure it to produce a phenolic foam; Including, The pH of the phenolic resin foam is 4 or more; The vertex of the cell of the phenolic resin foam was analyzed by EDX (energy dispersive X-ray spectroscopy). The mass ratio of carbon to sulfur (C / S) measured by energy dispersive X-ray analysis (EDXA) is 25 to 250, The apex of the cell of the phenolic resin foam was analyzed by EDX (energy dispersive X-ray spectroscopy). The mass ratio of oxygen to sulfur (O / S) measured by energy dispersive X-ray analysis (E X-ray analysis) is 5 to 60; A method for producing phenolic foam.

12. 11. A phenolic foam according to any one of claims 1 to 10, Thermal insulation material.

Citation Information

Patent Citations

  • Phenol resin foam material and manufacture

    JP1986185535A

  • Phenolic resin foam

    JP2009293033A

  • Expandable resol-type phenolic resin molding material, method for producing the same, and phenolic resin foam

    JP2010185061A

  • Phenolic resin foam laminate board and method for producing the same

    JP2016101750A

  • Phenol resin foam

    JP2017020049A